(untitled) (Research, Society and Development, 2021)
The pandemic of the new coronavirus, COVID-19, is the most discussed subject today, whether in the popular imagination, in media vehicles or in the pages of scientific literature. Given this biological problem, there was an increase in the use of social networks and other virtual platforms, resulting in a new form of social dynamics and interaction between individuals. Among the main negative effects of the intensive use of mobile phones, computers and other electronic devices, because of social isolation and other measures to restrict impositions, we mention the virtual prejudice and psychological changes of internet users, such as depression and anxiety. Therefore, the aim of this study is to understand the relationship between the exacerbated use of social media and COVID-19, evaluating whether cyberbullying is a risk factor for suicide in Brazil. Thus, through the literature analyzed, it was found that for refuge and relief from pain and suffering, due to social restrictions, individuals overuse virtual media, and may be hostages to self-destructive behaviors, which potentiate 1, such as self-mutilation and suicide.